Teledermatologia - Passado, presente e futuro - Miot, Hélio Amante [UNESP]; Paixão, Maurício Pedreira; Wen, Chao Lung (FapUNIFESP (SciELO), 2005)
Teledermatology is the area of Telemedicine that studies the application of telecommunication and information technology to dermatology practice without the presence of a specialist. It is a potential manner to deliver health planning, research, education, clinical meetings, second medical opinions and dermatological care to populations who cannot easily travel. The evolution, cost reduction and dissemination of telecommunication and information technology have enabled the implementation of low cost and comprehensive teledermatology systems to support clinical practice all over the world. © 2005 by Anais Brasileiros de Dermatologia.
Teledermatology - Past, present and future
Keywords: Dermatology; Health education; Remote consultation; Telemedicine; Brazil; clinical practice; clinical research; diagnostic procedure; follow up; health care cost; health care planning; human; information processing; information technology; legal aspect; leprosy; medical education; medical ethics; medical specialist; patient monitoring; review; skin cancer; teledermatology